Hearing Status of the Traffic Police with or without Use of Sound Protector in Dhaka Metropolitan City (Journal of Current and Advance Medical Research, 2018)
Background: Sound protector is an essential tool to protect hearing.Objective: The purpose of the present study was to see the hearing status of traffic police with or without sound protector.Methodology: The cross-sectional study was conducted in the Department of Otolaryngology and Head Neck Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2003 to June 2004 for a period of one and half year. Traffic police who were working in the Dhaka metropolitan city at any age were included as study population. Hearing status was measured to all subjects. The traffic police at any age working in the Dhaka metropolitan city with the duration of service more than 5 years were included as study population. Otoscopic examination, tuning fork test and pure tone audiometry were performed by clinical audiometer (AC 33) with two channels, with TDH39 earphones among the entire study subject.Result: A total number of 100 traffic polices working in Dhaka metropolitan city were examined. Highest (56%) number of the respondents was in between 30 to 40 years of age group. The mean age with SD was 36.15 ±5.5. In this study 53.0% respondents found to have exposure of 6 to 10 years and 16.0% found to have exposure between 16 to 20 years. It was found that 26 traffic police used ear protector occasionally. Among them 7(26.9%) subjects had different degree of hearing loss. Nonusers had higher rate (23%) of hearing loss (p=0.685).Conclusion: In conclusion use of sound protector by traffic police is not significantly related with the hearing loss though this is clinically significant.Journal of Current and Advance Medical Research 2017;4(1):13-16